New strategies to develop 'real' engagement by students with the learning of the knowledge and skills required for international competitiveness - Nowak, Margaret; Whiteley, Alma (Curtin University of Technology, 1994)
There is the assumption that the boundaries of functions and disciplines as they appear in organisations sometimes have their roots in the sort of management education provided by business schools. There is evidence that Australian companies espouse international competitiveness and especially the integrative aspect, but practice more ?traditional? and functional approaches, often mirroring the approaches in their professional and educational courses (Argyris, 1993). Management educators, and particularly those in business schools, need to take some responsibility for the current ?add-on? attitudes and activities which managers take back into organisations (Beck, Whiteley, and McFetridge, 1991). There needs to be corresponding management development in the practices of breaking down functional borders. The writers describe a holistic teaching/learning strategy designed to achieve deep rather than surface learning (Biggs, 1982). The vehicle for the paper is the ?International Business Competitiveness? (IBC) course of study offered to MBA students. The course unit involved a multi-disciplinary team of lecturers. It was recognised that this, in itself, would not solve the boundaries problem, indeed it could exacerbate it. Therefore, a model of international competitiveness was produced collaboratively by the lecturing team, and various integrating devices were designed. The paper will describe the model, the integrating devices, the qualitative evaluation methodology used and students? evaluative comments.